A Study on the Implementation of Universal Health Coverage Improvement in Coastal Communities in Selayar Islands Regency, South Sulawesi, Indonesia - Razak, Amran; Arifin, Muhammad Alwy; Palutturi, Sukri; Zuardin; Amran, Alfiah Ramadhani; Yani, Ahmad (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to analyze the implementation of Universal Health Coverage (UHC) in the fishermen communities in the Selayar Islands Regency based on 3 dimensions of UHC including membership, service and financial protection focused on fishermen who receive contribution assistance (PBI) -NHIS. This study is a qualitative research conducted through content analysis by observing the phenomena that occur. Data collection was carried out through 2 FGD groups (coastal villages and island villages) each consisting of 12 participants (n = 24) and in-depth interviews with 4 key informants and 10 other informants (n = 14). This study found that most of the fishermencommunities in the Selayar Islands Regencyhave benefited the NHIS program since it is free.The results revealed a special transportation request in the form of marine ambulance for emergency patients, medium capacity and managed by the community itself as an urgent need.In addition, the complexity of the use and claim of land ambulance services for underprivileged referral patients created its own economic difficulties. It was found that there were medical service providers which charged the costs of drugs and other procedures for referral patients who were also NHIS card holders from the poor and disadvantaged groups (Contribution Aid Assistance).